1998
DOI: 10.1046/j.1471-4159.1998.70031077.x
|View full text |Cite
|
Sign up to set email alerts
|

Release and Uptake Rates of 5‐Hydroxytryptamine in the Dorsal Raphe and Substantia Nigra Reticulata of the Rat Brain

Abstract: Fast scan cyclic voltammetry with carbon fiber electrodes has been used to investigate the dynamics of the neurotransmitter 5‐hydroxytryptamine (5‐HT) in the extracellular fluid of two brain regions: the dorsal raphe and the substantia nigra reticulata. The method used previously was shown to be optimized to allow the time course of 5‐HT concentration changes to be measured rapidly. Measurements were made in slices prepared from the brains of rats with the carbon fiber electrode inserted into the tissue and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 46 publications
15
116
0
Order By: Relevance
“…Previous studies have shown that the majority of brain monoamines resides in the vesicular storage pools and that pharmacological inhibition of VMAT prevents vesicular release of 5-HT (Adell and Artigas, 1998;Bunin et al, 1998;O'Connor and Kruk, 1991). We confirm here that VMAT2 is the only vesicular transporter implicated in this effect in the CNS, as its genetic ablation in 5-HT neurons entirely reproduced the effects on 5-HT uptake of complete VMAT inhibition with reserpine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that the majority of brain monoamines resides in the vesicular storage pools and that pharmacological inhibition of VMAT prevents vesicular release of 5-HT (Adell and Artigas, 1998;Bunin et al, 1998;O'Connor and Kruk, 1991). We confirm here that VMAT2 is the only vesicular transporter implicated in this effect in the CNS, as its genetic ablation in 5-HT neurons entirely reproduced the effects on 5-HT uptake of complete VMAT inhibition with reserpine.…”
Section: Discussionsupporting
confidence: 88%
“…Microdialysis (Adell and Artigas, 1998) and voltametry (Bunin et al, 1998; O'Connor and Kruk, 1991) experiments showed that tetrabenazine, a selective VMAT2 blocker, prevents the release of 5-HT in the raphe and in axon terminal fields, whereas VMAT2-KO mice showed no release of amines (Fon et al, 1997;Wang et al, 1997). VMAT2-KO mice do not survive beyond the first postnatal days Fon et al, 1997;Wang et al, 1997) preventing the long-term evaluation of the consequences of a lack of monoamine/5-HT release.…”
Section: Introductionmentioning
confidence: 99%
“…2 D) by the characteristic doublereduction current profile for 5-HT as noted previously in SNr (Davidson and Stamford, 1996;Cragg et al, 1997b;Iravani and Kruk, 1997;Bunin et al, 1998). Furthermore, it has been identified previously that the primary substance detected in rat SNr using this method is 5-HT and not DA (Cragg et al, 1997b;Iravani and Kruk, 1997;Bunin et al, 1998).…”
Section: Electrochemical Characterization Of 5-ht Release In Snrsupporting
confidence: 73%
“…Bath application of the SERT inhibitor citalopram (75 nM) prolonged the extracellular lifetime of 5-HT and significantly enhanced (Fig. 3A) (M-WU; p Ͻ 0.001; n ϭ 28) as shown previously with SERT inhibitors in the SNr (Iravani and Kruk, 1997;Bunin et al, 1998). Conversely, application of the DAT inhibitor GBR 12909 (1 M) had no effect on the lifetime or peak concentration of the detected substance, 5-HT (Fig.…”
Section: Electrochemical Characterization Of 5-ht Release In Snrsupporting
confidence: 70%
“…One of the advantages of cyclic voltammetry is multiple point identification (each cyclic voltammogram contains ϳ1000 points), which allows numerous species with unique oxidation and reduction potentials to be detected and differentiated. Fast-scan cyclic voltammetry can be used to detect catecholamines, indolamines, neurotransmitter metabolites, ascorbic acid, oxygen, nitric oxide, and pH changes (32,(42)(43)(44). The compounds detected and the ability to resolve two compounds can depend on the applied waveform.…”
Section: Chemical Selectivitymentioning
confidence: 99%